Anti-racist witchcraft. (July 2015) - Bourne, Jenny
In the light of the current discourse about national belonging in Britain/the UK, the author examines an episode in the 1980s when the same kind of debate was initiated by the Thatcherite Right over the work of the Institute of Race Relations (IRR) and its booklets for young people about the derivation and reality of racism. Accusing the IRR of political indoctrination, falsifying history, denigrating white people and redefining racism, attempts were made in parliament, the media, through a TV programme and a themed book, to ban the educational booklets of IRR, especially its cartoon book (which was blamed for inciting 'the riots' of 1985) and close down the organisation.